2011
DOI: 10.3390/s110707178
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Plasmonic Nanoantennas with Realistic 3D Roughness and Distortion

Abstract: Nanostructured plasmonic metamaterials, including optical nanoantenna arrays, are important for advanced optical sensing and imaging applications including surface-enhanced fluorescence, chemiluminescence, and Raman scattering. Although designs typically use ideally smooth geometries, realistic nanoantennas have nonzero roughness, which typically results in a modified enhancement factor that should be involved in their design. Herein we aim to treat roughness by introducing a realistic roughened geometry into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…It is well known that a nanoscale asperity of metals such as silver (Ag) generates localized SP resonance with intensified nearfield light. The roughness effect on the properties of metal films and particles [8][9][10][11], especially Ag superlens [12][13][14], has been investigated in some recent works. For example, it has been shown that quasi-periodic "roughness" can enhance the resolution of the superlens-based approach [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that a nanoscale asperity of metals such as silver (Ag) generates localized SP resonance with intensified nearfield light. The roughness effect on the properties of metal films and particles [8][9][10][11], especially Ag superlens [12][13][14], has been investigated in some recent works. For example, it has been shown that quasi-periodic "roughness" can enhance the resolution of the superlens-based approach [12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to account for the double-periodic nature of the array simulation, PMLs and SBCs were also placed at the top and the bottom of the unit cell and PECs (Perfect Electric Conditions, which nullify the electric field component perpendicular to the boundary surface) and PMCs (Perfect Magnetic Conditions, which nullify the magnetic field component perpendicular to the boundary surface) on its side walls. The PECs were placed on the two walls perpendicular to the polarization of the normal incident wave and the PMCs on the others, making the side walls act like mirrors, with the effect of a periodic array being obtained [15]. The separation of nanoantennas was equalized to that of the unit cell size.…”
Section: Methodsmentioning
confidence: 99%
“…In the following, we investigate this arm length sweep via simulations at three different level of abstraction, from ideal to realistic antenna structures. In our investigation we do not focus on the average influence of shape deviations as done in other publications as for example [16]. The nine chosen antennas on which the present investigation is based are rather representative samples of real shape deviations of different kinds and intensities.…”
Section: Simulationsmentioning
confidence: 99%
“…We believe that the main reason for this discrepancy is that especially the coupling between the two antenna arms is mainly influenced by the precise shape of the nanoantenna near the antenna gap. Furthermore, it has to be kept in mind that we do not average results from different shape configurations as done in [16] and partly in [18]. Of course, sample deviations can be much more pronounced than averaged deviations.…”
Section: Comparison Of Far Field Properties Of Antennas With Ideal Gementioning
confidence: 99%
See 1 more Smart Citation